PENEGAKAN HUKUM TERHADAP PELAKU PENGANGKUTAN DAN PENYIMPANAN BAHAN BAKAR MINYAK BERSUBSIDI ILEGAL BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2001 TENTANG MINYAK DAN GAS BUMI DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - Effendi, Erdianto; Edorita, Widia; ', Frengki (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Fuel scarcity happened recently has given a very broad impact in many areas of life. The sectors most affected are fast transport sector resulting in queues at most gas stations General. Scarcity of fuel oil that occurred in various provinces in Indonesia is one of Pekanbaru Riau Province in particular can not be separated from the less active surveillance and number of cases of the transport and storage of fuel oil illegal subsidies. In this case Pekanbaru City Police as law enforcement course is expected to run for the sake of justice in the community.In accordance with the above description, the authors are interested in doing research with the title of Law Enforcement Against Perpetrators of Transportation and Storage of Fuel Subsidized Illegal Under Act No. 22 of 2001 on Oil and Gas in the area of Pekanbaru City Police Law. Then to find out the constraints faced in the implementation of law enforcement transport and storage of fuel oil in the area of illegal subsidies Law Pekanbaru City Police. Finally aims to determine the barriers to the implementation of countermeasures for law enforcement transport and storage of fuel oil in the area of illegal subsidies Law Pekanbaru City Police.In writing this essay, the author uses empirical approach or sociological research. Regional research sites in Pekanbaru City Police Law. Data sources supported by the primary data source, secondary. While data collection techniques are interviews / interview and review of data using deductive method is to analyze the problems of a general nature and then drawn to a conclusion in particular based on existing theory.The results of the discussion in this paper is, first, that the crime of transporting and storage of fuel oil illegal subsidies Pekanbaru City Police has been working as it should, but have not optimal as expected. Both the lack of public awareness. Performers transport and storage of fuel oil subsidy Illegal organized, lack of facilities and infrastructure support. funds are limited, the suspect fled. Third, efforts made in addressing the crime of transporting and storage Actors Fuel subsidy Illegal Conduct effective and efficient action in managing the funds available, Capitalize infrastructure available, search and publish wanted list.Keywords: law enforcement, transportation and storage of fuel oil-illegal.